At My Doorstep - Jain, Nishtha (India, 2009)
The elite may be famous, but the lower class providers of services and goods in Bombay often remain faceless and nameless. They are mainly migrants, and their presence in India is sharply defined by the lack of survival options in their home country. They must also endure harsh conditions in order to survive in Bombay.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films